2022
DOI: 10.3390/w14203196
|View full text |Cite
|
Sign up to set email alerts
|

Age Structure and Spatial Distribution of Euphausia superba Larvae off the Antarctic Peninsula, Southern Ocean

Abstract: The Antarctic krill, Euphausia superba Dana, 1850, is a species forming high biomass and, therefore, playing a major role in the Antarctic marine food web. The age structure and patterns of spatial distribution of E. superba larvae in the waters of the Bransfield Strait (Antarctic Sound, Powell Basin), and off the South Orkney Islands, were studied based on data collected through a research survey in January and February 2022. Eggs and larvae (naupliar, calyptopis, and furcilia stages) of E. superba were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The highest euphausiid egg abundances were observed at the deep-sea stations which were associated with the highest oxygen concentrations (>10 mg/L), very cold water (−1 • C), and high, bloom-like phytoplankton concentrations. Mackintosh [91] found that euphausiid eggs and larvae at early stages tend to certain zones as the thermocline disappears; in addition, an abundance of krill larvae at early developmental stages may be associated with temperature and Chl a concentration [27,29,92,93]. Further studies are expected to be carried out to elucidate the relative contributions of the factors driving the abundance of copepods that dominate the mesozooplankton of the Southern Ocean and form the major food supply in the food chain between primary producers and predators [94,95].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The highest euphausiid egg abundances were observed at the deep-sea stations which were associated with the highest oxygen concentrations (>10 mg/L), very cold water (−1 • C), and high, bloom-like phytoplankton concentrations. Mackintosh [91] found that euphausiid eggs and larvae at early stages tend to certain zones as the thermocline disappears; in addition, an abundance of krill larvae at early developmental stages may be associated with temperature and Chl a concentration [27,29,92,93]. Further studies are expected to be carried out to elucidate the relative contributions of the factors driving the abundance of copepods that dominate the mesozooplankton of the Southern Ocean and form the major food supply in the food chain between primary producers and predators [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, data on the mesozooplankton together with the other plankton categories (phytoplankton, macroplankton, and ichthyoplankton) were obtained as preliminary results, e.g., [20,29]; in the present study, we provide more details and carried out additional analyses.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations